TEACHING TECHNIQUE FOR WRITING SKILL AT THE FOURTH SEMESTER STUDENTS OF BALIKPAPAN FOREIGN LANGUAGE ACADEMY IN THE ACADEMIC YEAR 2020/2021: A Descriptive Research - Muhammad Rochman (Journey: Journal of English Language and Pedagogy, 2022)
This study aims to describe teaching techniques for writing skills in The Fourth Semester Balikpapan Foreign Language Academy. This type of research is descriptive qualitative research. Sources of research data are events, informants, and documents. Collecting data from observations, interviews, and documents. Data is analyzed by reducing data, displaying data and verifying data. To show the truth of the data using triangulation data. The results showed that the techniques used by lecturers at Balikpapan Foreign Language Academy in teaching writing skills were using pictures, discussions, making groups and corrections, and presentations. The purpose of using techniques can make it easier for students to develop writing skills. The students' responses to each technique were interested and happy. Problems faced by lecturers such as passive students, vocabulary and writing structure problems, students’ difficulty developing paragraphs, and time constraints. Solutions for teaching writing skills include the lecturer encouraging students to be active, repeating the teaching of language and vocabulary structure, giving examples of making paragraphs using the correct tenses, motivating students to increase vocabulary, and the lecturer providing opportunities for students to practice writing not only once.